TINJAUAN YURIDIS TENTANG PERLINDUNGAN HUKUM KEPADA KARYAWAN TERKAIT WANPRESTASI DALAM PERJANJIAN KERJA WAKTU TERTENTU - Khairul Habibi; Arikha Saputra (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIH Awang Long, 2023)
The default case that occurred at PT Thania Indo Jaya against 2 (two) employees out of a total of 4 (four) employees with a Specific Time Work Agreement (PKWT) who was laid off due to the co-19 pandemic, namely not giving compensation rights to these employees. In this case, the Government is consistent in maintaining PKWT by issuing Perpu Number 2 of 2022 and Government Regulation Number 35 of 2021. The purpose of this study is to determine legal protection for PKWT employees at PT. Thania Indo Jaya Semarang and PKWT arrangements in laws and regulations, legal consequences in the event of default between the Company and employees. This study uses a type or type of normative juridical study. Data collection techniques are carried out through interviews, observation and documentation studies. The results of the study show that legal protection for PKWT employees at PT. Thania Indo Jaya Semarang is in the form of employment social security for employees, except for employees who are still apprentices, where employees who are still apprentices only get guarantees from the funeral service, provide work clothes and work tools, and form a P2K3 team. PT Thania Indo Jaya Semarang has committed a crime (default), so that it can be subject to a maximum imprisonment of 4 (four) years and/or a maximum fine of Rp. 400,000,000;- (four hundred million rupiah). Legal consequences if there is a default in the work agreement, which in the cancellation of the agreement is regulated in Articles 1451 and 1452 KUHP.